Beyond Donor–Acceptor (D–A) Approach: Structure–Optoelectronic Properties—Organic Photovoltaic Performance Correlation in New D–A1–D–A2 Low‐Bandgap Conjugated Polymers. Issue 7 (13th February 2017) - Chochos, Christos L.; Drakopoulou, Sofia; Katsouras, Athanasios; Squeo, Benedetta M.; Sprau, Christian; Colsmann, Alexander; Gregoriou, Vasilis G.; Cando, Alex‐Palma; Allard, Sybille; Scherf, Ullrich; Gasparini, Nicola; Kazerouni, Negar; et al.
Abstract : New low‐bandgap conjugated polymers have been developed based on the D–A1 –D–A2 approach . Systematic studies provide the first insights into how the nature of the monomers used to synthesize these new D–A1 –D–A2 low‐bandgap copolymers adjust the maximum absorption wavelengths, the optical and electrochemical bandgaps, the ionization potential and the electron affinity, and finally the organic photovoltaic performances. Abstract : Low‐bandgap near‐infrared polymers are usually synthesized using the common donor–acceptor (D–A) approach. However, recently polymer chemists are introducing more complex chemical concepts for better fine tuning of their optoelectronic properties. Usually these studies are limited to one or two polymer examples in each case study so far, though. In this study, the dependence of optoelectronic and macroscopic (device performance) properties in a series of six new D–A1 –D–A2 low bandgap semiconducting polymers is reported for the first time. Correlation between the chemical structure of single‐component polymer films and their optoelectronic properties has been achieved in terms of absorption maxima, optical bandgap, ionization potential, and electron affinity. Preliminary organic photovoltaic results based on blends of the D–A1 –D–A2 polymers as the electron donor mixed with the fullerene derivative [6, 6]‐phenyl‐C71 ‐butyric acid methyl ester demonstrate power conversion efficiencies close to 4% with short‐circuit current densities ( J sc ) of around 11 mA cm −2, high fill factors up to 0.70, and high open‐circuit voltages ( V oc s) of 0.70 V. All the devices are fabricated in an inverted architecture with the photoactive layer processed in air with doctor blade technique, showing the compatibility with roll‐to‐roll large‐scale manufacturing processes.